(untitled) (Journal of actual problems of jurisprudence, 2018)
The author of this article examines the development of the Institute’s presidency in the Republic of Kazakhstan and the consequent approval of the legal state of the Republic. Legal state exists as a certain theoretical concept. Right permeates the main spheres of the Kazakh society. After gaining independence in Kazakhstan, the formation of the rule of law and a new social order was carried out in all areas given the complex and in parallel in a single space, in the same period of time, within a social community. Considered ongoing legal, institutional, organizational and other activities. Key words: law, state, society president, board.